Micromechanical Modeling and Simulation of Forming Processes - Glavas, Vedran (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2017)
The deep drawing of an aluminum alloy used in the packaging industry for the beverage can manufacturing process is investigated. In this work, the effective constitutive behavior is based on a crystal plasticity model in combination with a non-linear Hashin-Shtrikman type homogenization scheme in which a reference stiffness controls the stress and strain fluctuations. The simulation results are compared to experiments in terms of deep drawing earing profiles, texture evolution, and localization.